PENERAPAN METODE DISCOVERY LEARNING DALAM PENINGKATAN HASIL BELAJAR BIOLOGI PADA SISWA SMA NASIONAL MAKASSAR - Nggeko, Herasmus; Karim, Syahruni; Sulfaidah, Sulfaidah (Guru Membangun, 2024)
The aim of this classroom action research is to determine the improvement in biology learning outcomes through Discovery Learning for class XII students at Makassar National High School. The subjects in this research were class Cycle I was held in 4 meetings and cycle II was also held in 4 meetings, including giving tests at the end of cycle I and cycle II. Data collection was carried out using student biology learning results tests and observation sheets. The data analysis technique uses quantitative analysis. The research results showed that the average value in cycle I was 64.75 which was in the medium category. In cycle II, the average value of biology learning outcomes was 76.62, which was in the high category. From the results of this research it can be concluded that by applying the Discovery Learning method in improving biology learning outcomes in class XII students at Makassar National High School can be increased to 80%